Semifluorinated alkane eye drops for treatment of dry eye disease due to meibomian gland disease - Steven, Philipp; Kaercher, Thomas; Kretz, Florian Tobias Alwin (Journal of ocular pharmacology and therapeutics, 2017)
Purpose: Meibomian gland disease is generally accepted as the leading cause for evaporative dry eye disease (DED). In a previous study, perfluorohexyloctane, a semifluorinated alkane, has been demonstrated to significantly increase tear film breakup time and to reduce corneal fluorescein staining in patients with evaporative DED, thereby vastly reducing dry eye-related symptoms. This study was set up to evaluate perfluorohexyloctane in a larger population of patients with Meibomian gland dysfunction.Methods: Seventy-two patients with Meibomian gland disease and associated dry eye received 1 drop of perfluorohexyloctane 4 times daily during an observational, prospective, multicenter, 6-8-week study. Clinical assessment included best-corrected visual acuity, intraocular pressure, Schirmer test I, tear film breakup time, anterior and posterior blepharitis assessment, number of expressible Meibomian glands, meibum quality and quantity, ocular surface fluorescein staining, lid margin and symptom assessment, and Ocular Surface Disease Index (OSDI©).Results: From the 72 patients recruited, 61 completed the trial per protocol. Nine patients did not apply the medication as recommended and 2 patients were lost to follow-up. Tear film breakup time, corneal and conjunctival fluorescein staining, number of expressible Meibomian glands, and severity of anterior and posterior blepharitis significantly improved after 6-8 weeks of perfluorohexyloctane application. In addition, symptoms improved as demonstrated by a significant decrease of OSDI-values from 37 (±13) to 26 (±16).Conclusions: In concordance with previous findings, 6-8 weeks of topical application of perfluorohexyloctane significantly improves clinical signs of Meibomian gland disease and associated mild to moderate DED.
Gesehen am 01.09.2020